The works of the Rev. John Wesley, Vol. 11 (of 32) - Wesley, John, 1703-1791 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Works of the Rev. John Wesley, Vol. 11" by John Wesley is a religious and spiritual collection written in the mid-18th century. This volume comprises a selection of writings that focus on the lives and deaths of notable religious figures, emphasizing their virtues, struggles, and experiences of faith. The text appears to be aimed at readers interested in Christian conduct, devotion, and the principles of Methodism, reflecting Wesley's own theological insights and pastoral concerns. The opening of this volume provides an array of instructive transcriber$1 (Bs notes to enhance readability for modern audiences, detailing the formation and structure of the text. It introduces a poignant account of Mr. Thomas Haliburton's final thoughts and reflections as he approaches death, illustrating his struggles with faith and the solace he finds in his relationship with God. This section encapsulates a heartfelt exhortation to his friends and family, urging them to remain faithful to God, showcasing themes of humility, divine grace, and the importance of being steadfast in one$1 (Bs faith even in the face of mortality. (This is an automatically generated summary.)s
Release date is 2024-05-13
Richard Hulse and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Theology -- Early works to 1800; Methodist Church; Theology -- History -- 18th century